Implementation of Islamic Religious Education Learning in Building Students' Social Attitude - Naima; Yaumi, Muhammad; Nursyam; Elya; Rahayu, Fitri (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This article discusses and analyzes the implementation of Islamic religious education learning and the supporting and inhibiting factors in shaping students' social attitudes at Balaroa Elementary School, Palu City. The type of research used in this research is qualitative field research using the Miles and Huberman analysis technique. The results showed that the implementation of Islamic religious education learning in Palu City consisted of three stages, namely initial activities, core activities, and closing activities. The supporting factor for Islamic religious education teaching at Balaroa Primary School is the addition of Islamic religious education class hours. Meanwhile, the inhibiting factors are the need for more motivation for some students and the lack of facilities and infrastructure to support learning. The analysis results show that the initial activities of Islamic religious education learning at SDN Balaroa can shape the social attitudes of students by forming an attitude of discipline, responsibility, and compassion for students. Likewise, the core learning activities can create and build an attitude of sympathy and empathy in students. Furthermore, the closing activities of Islamic religious education learning can also form an open attitude and the ability to work with students. Thus, implementing Islamic religious education at SDN Balaroa has implications for forming social attitudes in students.